그린리모델링 기술요소 적용에 따른 단독 및 공동주택의 에너지 저감 효과 분석 - 정수빈(Jeong Subin); 김진희(Kim Jinhee); 김준태(Kim Juntae) (한국태양에너지학회 논문집, 2024)
Green remodeling has been proposed as a carbon-reduction methodology for existing buildings in Korea. Notably, residential buildings account for 46% of the total existing buildings in Korea. Among these, residential buildings older than 15 years account for approximately 67%; therefore, green remodeling is essential for reducing greenhouse gas emissions. However, previous research has been limited to analyzing the energy performance of green remodeling technology elements in residential buildings. Therefore, the present study examined the energy performance of old housing models based on the elapsed age of apartments and single-family houses through the application of green remodeling elements. Applying photovoltaic power generation facilities is the most advantageous method to reduce primary energy consumption in the lifetimes of both apartments and single-family houses, and the shorter the elapsed life, the greater the energy-saving rate. Building Attached Photovoltaic (BAPV) system elements were the most advantageous for energy savings in all elapsed years. Specifically, the maximum reduction in primary energy consumption was 22.3% for apartments and 30.8% for single-family houses. In addition to the technological elements of new and renewable energy, the application of passive design is advantageous for energy saving in both single-family and multi-family houses, and the shorter the elapsed life, the more beneficial the application of active design is for energy saving. KCI Citation Count: 0